Case Report: Refractory Chronic Spontaneous Urticaria Treated With Omalizumab in an Adolescent With Crohn’s Disease - Barni, Simona; Giovannini, Mattia; Liccioli, Giulia; Sarti, Lucrezia; Gissi, Anna; Lionetti, Paolo; Mori, Francesca (Frontiers in Immunology, 2021)
Chronic spontaneous urticaria (CSU) is a mast cell-driven disease that is often associated with autoimmune or autoinflammatory conditions. Omalizumab is recommended in the treatment of refractory CSU in patients over 12 years of age who do not respond to four standard doses of antihistamines. Omalizumab blocks the mast cells’ degranulation, thus interrupting the resulting inflammatory cascade driven by T-helper 2 (Th2) cytokines. The efficacy of omalizumab in controlling CSU and possible associated diseases has been studied in few patients so far. In particular, some case reports describe adults with CSU and concomitant inflammatory bowel diseases (IBD), such as Crohn’s disease (CD) or ulcerative colitis (UC). Although the treatment of CD with anti-tumor necrosis factors-α (TNF-α) seems to be effective in controlling CSU, no cases of the utility of omalizumab in patients with both conditions have been described so far. At the moment, there is no evidence that the pathogenetic mechanisms underlying CD are linked to the same pathways that are inhibited by omalizumab for the treatment of CSU. We present the first pediatric case of refractory CSU and CD in which omalizumab led to CSU remission, even if the follow-up period was limited. In conclusion, our experience shows how CSU could be associated with CD and successfully treated with the monoclonal anti-IgE antibody in a patient on immunosuppressive therapy. However, more data is needed from a larger population.